Treatment Effects Produced by Fränkel Appliance in Patients with Class II, Division 1 Malocclusion - De Almeida, Marcio Rodrigues; Henriques, José Fernando Castanha; De Almeida, Renato Rodrigues; Ursi, Weber [UNESP] (My University, 2002)
The purpose of this investigation was to evaluate the dentoalveolar and skeletal cephalometric changes produced by the Fränkel appliance in individuals with a Class II, division 1 malocclusion. Lateral cephalograms of 44 patients of both sexes were divided in two groups of 22 each. The control group was comprised of untreated Class II children with an initial mean age of eight years and seven months who were followed without treatment for a period of 13 months. The Fränkel group had an initial mean age of nine years and was treated for a mean period of 17 months. Lateral cephalometric headfilms of each patient were obtained at the beginning and end of treatment. The Fränkel appliance produced no significant changes in maxillary growth during the evaluation period, while a statistically significant increase in mandibular length was observed. The maxillomandibular relationship improved mostly because of an increase in mandibular length. In addition, there were no statistically significant differences in the craniofacial growth direction between the Fränkel and the control group, both showing a slight downward rotation of the palatal plane. The Fränkel appliance produced a labial tipping of the lower incisors and a lingual inclination of the upper incisors as well as a significant increase in mandibular posterior dentoalveolar height. It was concluded that the main effects of the Fränkel appliance during this time period were mostly dentoalveolar with a smaller but significant skeletal mandibular effect.
Keywords: Class II, division 1 malocclusion; Functional orthopedics; Functional Regulator appliance; cephalometry; child; female; follow up; growth, development and aging; human; image processing; incisor; jaw; male; malocclusion; mandible; maxilla; maxillofacial development; orthodontic device; palate; pathology; rotation; sex difference; statistical analysis; statistics; treatment outcome; Alveolar Process; Cephalometry; Child; Female; Follow-Up Studies; Humans; Image Processing, Computer-Assisted; Incisor; Male; Malocclusion, Angle Class II; Mandible; Matched-Pair Analysis; Maxilla; Maxillofacial Development; Orthodontic Appliances, Functional; Palate; Rotation; Sex Factors; Statistics; Treatment Outcome